N-heterocyclic carbenes and their applications for nanomaterials - Mascia, Rossella (2018)
This thesis reports on the synthesis of metallic Ni nanoparticles (NiNP) stabilised by N-heterocyclic carbenes (NHCs) carbene and trioctylphosphine (TOP). The synthetic procedure is based on the formation of a nickelacetylacetonate-oleylamine complex followed by the addition of the stabiliser. The NHCs are synthesised using two precursors; 2,6-dibromopyridine and benzimidazole. The precursors undergo alkylation to form the final product used as stabilising agent (capping agent). The stabilisers are chemically and physically characterised by NMR (Nuclear Magnetic Resonance), MS (Mass Spectrometry), CHN elemental analysis, TGA (Thermo Gravimetric Analysis) and XPS (X-Ray Photoemission Spectroscopy). TGA allows a comprehensive understanding of their thermal stability properties at varies temperature ranges. XPS analysis has been shown as a powerful tool to probe the electronic environment of the ionic compound structures, which allows correlating the binding energy to the different types of elements presents. Both the C1s and the N1s fitting models for the [(CnBzIm)2Py]X2 are presented. The symmetry of the molecule represents a unique opportunity to assess the fitting model of the NHCs previously investigated only for geminal ILs. The new nickel nanoparticles are synthesised through thermal decomposition of nickel acetylacetonate-oleylamine complex. To identify the morphology of the NiNPs complementary electron and spectroscopy techniques are used. The Ni-NHCs and Ni-TOP nanoparticles are inserted in graphitised nanofibers using a well-known filling technique based on capillary forces. The new hybrid structures NiNPs@GNF are tested to tentatively explore their potential applications as electrochemical nanoreactors.